Innovation of IBS 3D printing mix design material tensile performance with Kenaf fibre / Muhammad Amirul Haqim Saharan and Muhammad Naim Mahyuddin - Saharan, Muhammad Amirul Haqim; Mahyuddin, Muhammad Naim (2023)
The construction industry has experienced a paradigm shift, leading to a growing demand for sustainable construction methods. 3D printing technology has revolutionised the construction industry by allowing for mass-customisation of structures, reducing the need for formwork and labour. However, 3D printing has faced challenges due to unstable and low-strength materials, making it an expensive method. This research aims to find a sustainable material for 3D printing technology in the construction industry, ensuring its strength, cost, and handling methods are superior to those of existing materials. The use of natural building materials from plant waste is crucial for reducing the cost of construction using 3D printing technology in a country.